2012
DOI: 10.1186/1471-244x-12-237
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality and its psychological correlates among university students in Ethiopia: a cross-sectional study

Abstract: BackgroundSleep is an important physiological process for humans. University students in most resource limited countries often report poor sleep quality due to changing social opportunities and increasing academic demands. However, sleep quality among university students has not been studied in Ethiopia. Thus, this study assessed sleep quality and its demographic and psychological correlates among university students.MethodsA cross-sectional survey was conducted in two universities in Ethiopia. Multistage samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

47
222
13
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(296 citation statements)
references
References 25 publications
47
222
13
14
Order By: Relevance
“…Last, some studies also report positive correlations between sleep quality or sleep duration on the one hand and grade point averages and exam passing probabilities on the other hand in tertiary education in China, Ethiopia, Germany and Portugal (Ahrberg et al, 2012;Genzel et al, 2013;Gomes, 2011;Lemma et al, 2014;Wong et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Last, some studies also report positive correlations between sleep quality or sleep duration on the one hand and grade point averages and exam passing probabilities on the other hand in tertiary education in China, Ethiopia, Germany and Portugal (Ahrberg et al, 2012;Genzel et al, 2013;Gomes, 2011;Lemma et al, 2014;Wong et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…In general, antianxiety drugs are also effective for the improvement of sleep because psychological disorders such as stress, depression and anxiety are deeply involved in sleep quality (9,10). GABA is known to have effects of anti-stress and relaxation (3)(4)(5)(6), and AVLE is also effective for relieving depression (7) and anxiety (8).…”
Section: Discussionmentioning
confidence: 99%
“…2), shows antidepressant effects (7) and antianxiety and antihypertensive activities (8). Since both GABA and AVLE have effects on psychological disorders, which are deeply involved in sleep quality (9,10), the improvement of sleep can be expected from ingestion of them. In fact, GABA has been reported to help elderly people to sleep well (11), and AVLE has been recorded in 'Pharmacopoeia of People's Republic of China' and used as an herbal medicine to treat insomnia in China (12).…”
mentioning
confidence: 99%
“…In addition, complaints of insomnia or poor sleep quality have been consistently reported in higher-education students in a variety of countries from all continents (e.g. Alapin et al, 2000;Allen Gomes et al, 2009;Fernández-Mendoza et al, 2009;Lack, 1986;Lemma et al, 2012;Lima et al, 2002;Lohsoonthorn, 2013;Machado et al, 1998;Taylor et al, 2013;Wong et al, 2013). Therefore, it seems that insomnia symptoms and poor sleep quality complaints in undergraduate/graduate students deserve more attention.…”
Section: Introductionmentioning
confidence: 99%
“…However, even in such samples with a majority of reasonably healthy individuals, sleep quality assessed by different methods has been associated with a myriad of daytime correlates, such as academic achievement (Lemma et al, 2013;Tavernier & Willoughby, 2013;Wong et al, 2013), psychosocial functioning (e.g. friendship quality; self-esteem) (Tavernier & Willoughby, 2013), neuroticism, social support (Cheng et al, 2012), reported health (Cheng et al, 2012;Pilcher et al, 1997;Wong et al, 2013), wellbeing indicators (Pilcher et al, 1997), perceived stress level, and symptoms of depression and anxiety (Lemma et al, 2012;Wong et al, 2013). In addition, complaints of insomnia or poor sleep quality have been consistently reported in higher-education students in a variety of countries from all continents (e.g.…”
Section: Introductionmentioning
confidence: 99%